2017
DOI: 10.1016/j.bbadis.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNA biogenesis in the small intestine after ethanol and burn injury

Abstract: Ethanol exposure at the time of burn injury is a major contributor to post-burn pathogenesis. Many of the adverse effects associated with ethanol and burn injury are linked to an impaired intestinal barrier. The combined insult causes intestinal inflammation, resulting in tissue damage, altered tight junction expression, and increased intestinal permeability. microRNAs play a critical role in maintaining intestinal homeostasis including intestinal inflammation and barrier function. Specifically, miR-150 regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
(76 reference statements)
1
20
0
Order By: Relevance
“…MicroRNAs (miRNAs) are short non-coding RNA sequences that play critical roles in a variety of physiological and pathological processes (Fromm et al, 2015). Burn injury, disease and some other factors could change the expressions of miRNAs and therefore negatively affect intestinal homeostasis (Morris et al, 2017). MiR-320 is a member of the miRNAs (Song et al, 2014), to date, evidence demonstrated that miR-320 was involved in a variety of pathological processes, including myocardial ischemia reperfusion injury, and it is associated with cell proliferation, apoptosis and death (Zhang et al, 2016) .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are short non-coding RNA sequences that play critical roles in a variety of physiological and pathological processes (Fromm et al, 2015). Burn injury, disease and some other factors could change the expressions of miRNAs and therefore negatively affect intestinal homeostasis (Morris et al, 2017). MiR-320 is a member of the miRNAs (Song et al, 2014), to date, evidence demonstrated that miR-320 was involved in a variety of pathological processes, including myocardial ischemia reperfusion injury, and it is associated with cell proliferation, apoptosis and death (Zhang et al, 2016) .…”
Section: Discussionmentioning
confidence: 99%
“…Altered expressions of miRs have been associated with altered intestinal barrier function affecting components such as tight junction protein and mucins. In particular, miR-150 has been shown to have a role in mediating inflammation, [20][21][22] which is a major adverse effect following the combined insult of ethanol and burn injury. 11,12 Similarly, other miRs such as miR-7a have roles in regulating components of the intestinal barrier such as inflammation.…”
mentioning
confidence: 99%
“…Numerous studies demonstrate that alcohol exacerbates adverse effects to the gut following injury and disease [82,87,91,92,93]. In a two-hit model of co-exposure of colon cancer cell lines to alcohol and/or arsenic, alcohol or arsenic alone increased ROS production; however, there were additive effects when alcohol and arsenic exposure were combined.…”
Section: The Role Of Hif-1α In Alcohol-mediated Intestinal Damagementioning
confidence: 99%